Contrasting Early Palaeozoic provenance of the Yemaquan and Harlik arcs in the SW Altaids (NW China): identification of cryptic sutures in accretionary orogens. Issue 17 (22nd November 2021) - Li, Liang; Xiao, Wenjiao; Windley, Brian F.; Mao, Qigui; Jia, Xiaoliang; Yang, He; Tan, Zhou; Sang, Miao; Gan, Jingmin; Abuduxun, Nijiati
ABSTRACT: The means and timing of amalgamation of the Harlik arc to the Yemaquan arc remain controversial. To address these polemic relations, we report new field data and zircon U-Pb analyses of early Palaeozoic strata in the Harlik Mountains. Field investigations reveal that the Huangcaopo Group in northern Harlik are composed mainly of clastic rocks, while their counterparts in central Harlik (Harlik arc) are dominantly volcanic and pyroclastic rocks. Weighted mean ages of the youngest group of samples from northern Harlik are 455 ± 9 Ma and 456 ± 7 Ma, whereas their counterparts in central Harlik have a weighted mean age of 446 ± 4 Ma, indicating that parts of the Huangcaopo Group in central Harlik should be re-defined as the early Silurian Hongliuxia Formation. The youngest grain from the Dananhu Formation in central Harlik is 421 ± 3 Ma, the time of deposition in early Devonian. Age spectra of the Huangcaopo Group in northern Harlik have only two peaks at 488 Ma and 923 Ma, demonstrating affinity with the Tuva-Mongolian microcontinent, a correlation supported by the occurrence of Silurian Tuvaella brachiopod fauna in those strata. In contrast, multiple peaks at 494 Ma, 813 Ma, 1485 Ma, 1872 Ma and 2469 Ma in the Hongliuxia and Dananhu Formations in central Harlik have neither an affinity with the Tuva-Mongolian nor with the Central Tianshan microcontinent, which suggests that the Harlik arc probably evolved independently as a Japan-type arc in the early Palaeozoic. The above disparate relations, combined with the fact that the Silurian Tuvaella brachiopod fauna occurs throughout the Kelameili ophiolite belt but not in the Harlik arc, provide robust evidence that the contrasting provenance of the Yemaquan and Harlik arcs is an expression of a cryptic suture in northern Harlik rather than along the Kelameili ophiolite belt to the north.